Analisis Pembayaran Klaim PT. Jamsostek (Persero) pada Karyawan Bank Lampung Di Bandar Lampung Berdasarkan Undang-Undang Nomor 3 Tahun 1992 Tentang Jaminan Sosial Tenaga Kerja - Tami Rusli (Law Faculty of Universitas Bandar Lampung, 2013)
National development has evolved over the employment opportunities for the people of Indonesia, so as to obtain income to meet the needs of workers and their families live. However, the ability to work and earn the opportunities and diminished or lost due to a variety of risk experienced workforce. Implementation of the Payment Claim made by PT. Social Security (Persero) Bank Employees Lampung To Happen When Evenemen In carrying out the payment of claims of PT. Social Security. Implementation completed in accordance with claim payments evenemen happened by 4 (four) social security programs such labor. Factors supporting the implementation of the payment of social security claims in PT. Social Security (Persero) in Lampung Bank employees are: the Law No. 3 of 1992, Act No. 13 of 2003 and Government Regulation No. 14 of 1992.